Portuguese Version of the Cyber Pornography Use Inventory-9: Psychometric Properties and Gender Invariance. Issue 7 (3rd October 2019) - Cardoso, Jorge; Ramos, Catarina; Almeida, Telma
Abstract: We aimed to analyze the factor structure and the psychometric properties of the Portuguese version of the Cyber Pornography Use Inventory-9 (CPUI-9) and to verify the invariance between men and women. A total sample of 257 university students (153 women and 104 men) participated through a web survey. The results of confirmatory factor analysis showed that the three-factor structure of the original version of the CPUI-9 has a good model fit and good convergent and discriminant validities. The findings of the multigroup confirmatory factor analysis demonstrated non-invariance on factor structure across both genders, suggesting that the CPUI-9 should be applied with caution to men and women.